Ruins and Legitimacy in Massinga. Ways of Thinking the Past among Impoverished Elders in Southern Mozambique - Farré, Albert (Revista de Antropología Social, 2016)
Drawing from ethnographic fieldwork in Massinga district, this article presents the building up of traditional authority’s legitimacy as a process linked to southern Africa regional history. Both the colonial State and the mining industry transformed African societies. Rural migrants, despite being confined to the customary sphere, were in fact straddling two different systems of social reproduction, as for successful young proletarians would become respected traditional elders. Thanks to this ambiguous position, each generation of migrants was able to build new and fancy houses. By doing so, they also contributed to renewing the legitimacy of traditional institutions. Once the mines stopped the recruitment of Mozambican young miners, the usual way to renew legitimacy collapsed.
Keywords: traditional authority; State; labour migration; rite of passage; generation gap.